Abandono e institucionalização de crianças: significados e sentidos - Orionte, Ivana (2004)
This study aims at understanding the significance and meanings attributed by abandoned children who are at a sheltering institution in the city of Goiania, GO, Brazil. To constitute the research design, strategies such as participator observation, semi-structured interviews, sentence-completion techniques, drawings and stories from children s books were used with five children, being three males and two females. Vigotsky s historic-cultural approach constitutes the theoretical basis upon which this research was developed, interconnected with González Rey s epistemology and qualitative methodology, and his content analysis approach for analyzing children s speech. A brief historic overview was made on the issue of abandoned children in Brazil, in which historical contexts are presented up to the present time, as well as the conditions for institutionalizing children before and after the ECA, the Child and Adolescent Act. Findings from the studied children and their speech are that although ECA guarantees children a place as subjects with rights, an adult centered view still dominates and tries to shut children s voices. This research, thus, tries to understand the significance and meanings of abandonment for the children from that particular instituion and how it echoes in the constitution of their subjectivities. The contents revealed from the analysis of the children s speech might alert the authorities about the importance of having children participate actively in the planning of public policies related to children, as well as the importance of the investment, within the institutions, not only on the pedagogical and structural factors, but also on the human factor, considered beyond the professional skills, in order to include the caring and emotional dimensions which are fundamental to the constituion of self-governing and healthy subjectivities.